Juridical Message in the Shadow of the Carceral: Prison Discipline, Additional Days and the Feasibility of Penal Communication. (December 2021) - Dagan, Netanel
Juridical and carceral scholarship seldom interact. As a result, the visible and less visible intersections and gaps between the two penal logics and discourses are often overlooked. The paper argues for better understanding of juridical power, and how it may cut through the boundaries of juridical/carceral separation. As a case study, the paper problematises the disciplinary punishment of imposing 'additional days' of prison time (AD) for prison rules violations, through the lenses of communicative sentencing theory. The paper argues that AD may undermine the juridical communicative ideal as it may cause penal censure to lose credibility, trivialise the value of prison time, and harm the feasibility of penal communication by disconnecting imprisonment from the offence of conviction. Conclusions for socio-legal and penal theory and policy are discussed.